Computer Science &Amp; Information Technology ( CS &Amp; IT ) 2015
DOI: 10.5121/csit.2015.51508
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors (CSFS) of Enterprise Resource Planning (ERP) System Implementation in Higher Education Institutions (HEIS) : Concepts and Literature Review

Abstract: Nowadays, Information Technology (IT) plays an important role in efficiency and effectiveness of the organizational performance. As an IT application, Enterprise Resource Planning (ERP) systems is considered one of the most important IT applications because it enables the organizations to connect and interact with its administrative units in order to manage data and organize internal procedures. Many institutions use ERP systems, most notably Higher Education Institutions (HEIs). However, many projects fail or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The external factors covered vendor support and consultant competency. Authors in [17] defined critical success factors (CSFs) contributing to the success of ERP implementation in Saudi Arabia. The research identified 13 most important ERP CSFs, extracted from previous studies in this field.…”
Section: A Determinants Of Success Of Erp Adoptionmentioning
confidence: 99%
“…The external factors covered vendor support and consultant competency. Authors in [17] defined critical success factors (CSFs) contributing to the success of ERP implementation in Saudi Arabia. The research identified 13 most important ERP CSFs, extracted from previous studies in this field.…”
Section: A Determinants Of Success Of Erp Adoptionmentioning
confidence: 99%
“…In addition, there are many previously identified factors that could influence the successful implementation of ERP systems. Recently, universities have implemented ERP systems, but there is a lack of research focusing on the implementation of ERP systems in the HEI sector around the world [26,29,78,79]. Furthermore, some studies have identified the urgent need to identify success factors that lead to the successful implementation of the system, as failure rate of ERP systems in HEIs is higher than that in the business sector [11 , 30].…”
Section: Success Factors For Erp Implementation In Heismentioning
confidence: 99%
“…Some previous researchers have tried to identify the strategy to succeed in ERP implementation. Many of them suggest critical success factors of ERP implementation in general (Al-Mashari et al, 2003;Zhang, Lee, Zhang, & Banerjee, 2003;Leyh, 2012;Ahmad & Cuenca, 2013;Dantes & Hasibuan, 2011;AlQashami & Heba, 2015;Puspitaningrum & Sintiya, 2018;Mahraz et al, 2018). However, modified ERP implementation needs specific critical success factors that should be elaborated.…”
Section: Erp Misfitmentioning
confidence: 99%